Supporting the Use of Scientific Literature in Preschool Teacher Education - Olsson, Ingrid (Högre utbildning, 2025)
This qualitative study aimed to build knowledge of preschool teacher training students’ perspectives on teaching practices that facilitate use of knowledge from scientific literature to understand preschool practices. The article reports how 82 participants, enrolled as students in the second half of their preschool teacher training, suggested that university teachers could help students use scientific literature and how their suggestions can be understood by using theoretical concepts from the didactic triangle, support and demand, and trust. Data were collected through the participants’ written answers to an open-ended question and were analysed with qualitative methods. The results indicated that students find it challenging to use scientific literature. Various suggestions emerged for teaching practices that can be used by teachers to support students. These practices were related to preparations before and teaching during classes in which students are expected to use scientific literature. The results are discussed in relation to the need for future research to develop higher education practices that meet the needs of all students.